THE APPLICATION OF BLOCKCHAIN TECHNOLOGY AND SMART CONTRACTS IN SHARIA FINTECH: OPPORTUNITIES AND CHALLENGES - Mabrur, Imam; Agustina, Ahadiah (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
The rapid growth of financial technology (fintech) has transformed the global economic landscape, including the Islamic finance sector, which seeks to align innovation with Shariah principles. This study aims to analyze the opportunities and challenges of applying blockchain technology and smart contracts in the Islamic fintech ecosystem, particularly in the context of strengthening Islamic financial principles in the digital era. It employs a Systematic Literature Review (SLR) approach combined with qualitative descriptive analysis of fifteen scientific articles indexed in Scopus, ScienceDirect, Garuda, and Sinta, covering the period from 2020 to 2025. The data was analyzed thematically to identify patterns of findings, research gaps, and academic and practical implications. The results indicate that blockchain technology and smart contracts have the potential to enhance transparency, efficiency, and accountability in Islamic financial transactions. Their implementation also opens opportunities for product innovation, such as smart sukuk and Islamic crowdfunding, which foster Shariah-based financial inclusion. However, challenges remain, including unclear Shariah digital regulations, technological complexity, low digital literacy, and issues of ethics and data security. The synthesis of findings highlights the need for collaboration among regulators, technology experts, and scholars to develop adaptive and Shariah-compliant fintech standards.